Determination of Silver in Metal Plating Wastewater by Slotted Quartz Tube Flame Atomic Absorption Spectrometry (SQT-FAAS) after Preconcentration with Stearic Acid-Coated Magnetite Nanoparticle-Based Solid-Phase Microextraction (SA-MNP-SPME). (3rd May 2022) - Serbest, Hakan; Bakırdere, Sezgin; Keyf, Seyfullah
Abstract: Here is reported the determination of silver at ultratrace levels by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) following stearic acid coated magnetic nanoparticle based solid phase microextraction (SA-MNP-SPME). The parameters affecting silver extraction were optimized to obtain high efficiency. In addition to the magnetic property of iron oxide (Fe3 O4 ) nanoparticles, they were coated with stearic acid to increase the surface area and the capacity for the analyte. An external magnetic field was used to separate the silver from the liquid phase. To obtain the highest efficiency, the mass of magnetic nanoparticles, pH and volume of buffer solution, mixing type and period, volume of eluent and volume of sample were optimized univariately. Under the optimum conditions, the limits of detection and quantitation were determined to be 40 and 130 ng L −1, respectively. Recovery experiments were performed to investigate matrix effects on the developed method by spiking real samples. Recoveries were between 96.3 and 105.1% with low standard deviations by the matrix matching calibration. The developed MNP-SPME-SQT-FAAS method achieved 305-fold improvement in detection power. These results demonstrated the method's applicability for the determination of trace silver in complex samples with good accuracy and precision.